The impacts of organizational change towards employees‘ performance in banking industry. - Lam, Wai Fong; Lau, Wai Ting; Ng, Mei Hui; Shua, Hui Ying; Teh, Soo Ee (2011)
The main objective of this research is to analyze the impacts of organizational changes towards employees‘ performance in banking industry. The factors that will be discussed in the chapter include communication, leadership, procedural justice, employees‘ development and tolerance to change. The previous study by other researchers will helps to develop the hypotheses in this research project. The location that been selected are Penang, Kuala Lumpur, Johor Bahru and Selangor. A sample size of 200 respondents in the questionnaire had been conducted. The questionnaire was design and distributed through randomly sample to employees. The Statistical Package for Social Science (SPSS) software had been used in order to run the reliability analysis, frequency analysis, explaining the correlation coefficient analysis and test of hypothesized relationships among the dependent variable and the independent variables. As a result, it had been found that communication, procedural justice, employees‘ development and tolerance to change has positive significant relationship with employees‘ performance. On the other hand, leadership has the negative significant relationship with employees‘ performance. Next, the findings and suggested recommendation have been discussed. Lastly, the future study and conclusion have been done.